Analysis of Information Technology Governance Using Domain EDM in the SMP XYZ Jakarta - Fernando, Erick; Denny Prabowo, Yulius; Gatc, Jullend (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
The main goal of this study is to assess SMP XYZ Jakarta's IT governance implementation and maturity. This report provides a complete analysis, strategic recommendations, and strategies for enhancing system efficiency and functionality to improve operational outcomes. A COBIT 5 maturity value evaluation at SMP XYZ Jakarta found GAP Analysis shortcomings in many domains. In particular, EDM01 and EDM02 exhibit possible governance structure and benefit distribution concerns with discrepancies of -0.33 and -0.16, respectively. Risk optimization is substantial for EDM03, which has a positive disparity of 0.34. EDM04 emphasizes efficient resource allocation with a differential of -0.33, whereas EDM05 signals stakeholder transparency needs with 0.17. The governance structure's strengths and weaknesses are shown by the average domain disparity of -0.31. Data from questionnaires reveal proficiency in subdomains like EDM01 governance framework construction. Also noted were benefits delivery (EDM02) and risk optimization (EDM03). EDM04 and EDM05's predicted level 3 progress supports SMP XYZ Jakarta's ambitious governance framework improvement target.